2015
DOI: 10.1021/acs.jpcc.5b03295
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Location and Ti–O Bond Distances in Pristine and N-Doped TiO2 Anatase Thin Films by X-ray Absorption Studies

Abstract: 2This paper reports detailed EXAFS analysis of spray pyrolysis synthesized TiO 2 thin films to, 3 locate position of nitrogen in N-doped phase pure(anatase)TiO 2 , evaluate Ti-O bond distances 4 and the co-ordination number of Ti. The thin films were synthesized at three different substrate 5 temperatures viz. 400, 450 and 500 o C leading to concomitant occurrence of varying nitrogen 6 concentration (N/Ti) of 0.282, 0.237, 0.24 respectively. The co-ordination number extracted 7 from the EXAFS fitting revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…EXAFS data analysis was carried out in order to determine the position of the dopants in the titania samples using a similar approach to that reported by Sahoo et al 32 . Crystallographic data for TiO 2 anatase reference phase was used to construct the model for fitting the spectra.…”
Section: Structural Features Of N-doped and Oxygen-rich Titaniamentioning
confidence: 99%
See 1 more Smart Citation
“…EXAFS data analysis was carried out in order to determine the position of the dopants in the titania samples using a similar approach to that reported by Sahoo et al 32 . Crystallographic data for TiO 2 anatase reference phase was used to construct the model for fitting the spectra.…”
Section: Structural Features Of N-doped and Oxygen-rich Titaniamentioning
confidence: 99%
“…In a more recent investigation supported by DFT calculations and EXAFS, Ceotto et al postulated that nitrogen preferentially occupies the axial position in the TiO 6 polyhedra replacing the lattice oxygen at low doping levels and forming oxygen-vacancies at high dopant concentrations 31 . Several years later, Sahoo et al found out by means of EXAFS that the nitrogen interstitial doping is responsible for the reduction of Ti-O coordination number and the increase of the axial and equatorial Ti-O bond lengths 32 .…”
mentioning
confidence: 99%
“…The normalised XANES spectra of the Mn doped TiO 2 thin films at Ti K‐edge are shown in Figure . The absorption edge position clearly indicates that Ti is present in +4 oxidation state and the XANES spectral features for undoped TiO 2 sample exactly resemble that of anatase TiO 2 . The white line observed for TiO 2 is transition of 1 s electron to the vacant np orbital of Ti or the anti‐bonding orbital of Ti−O.…”
Section: Resultsmentioning
confidence: 78%
“…Fig. 10(a 53,54 These three pre-edge peaks intensities were related to the symmetry of the crystal structure. A distortion and oxygen vacancies can cause an increase in the pre-edge intensity.…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%